Exploiting flux shadowing for strain and bending engineering in core–shell nanowires. Issue 5 (11th January 2023) - Al Humaidi, Mahmoud; Jakob, Julian; Al Hassan, Ali; Davtyan, Arman; Schroth, Philipp; Feigl, Ludwig; Herranz, Jesús; Novikov, Dmitri; Geelhaar, Lutz; Baumbach, Tilo; Pietsch, Ullrich
Abstract : Here we report on the non-uniform shell growth of In x Ga1− x As on the GaAs nanowire (NW) core by molecular beam epitaxy (MBE). Abstract : Here we report on the non-uniform shell growth of In x Ga1− x As on the GaAs nanowire (NW) core by molecular beam epitaxy (MBE). The growth was realized on pre-patterned silicon substrates with the pitch size ( p ) ranging from 0.1 μm to 10 μm. Considering the preferable bending direction with respect to the MBE cells as well as the layout of the substrate pattern, we were able to modify the strain distribution along the NW growth axis and the subsequent bending profile. For NW arrays with a high number density, the obtained bending profile of the NWs is composed of straight (barely-strained) and bent (strained) segments with different lengths which depend on the pitch size. A precise control of the bent and straight NW segment length provides a method to design NW based devices with length selective strain distribution.